PENGARUH ORANG, BUKTI FISIK DAN PROSES TERHADAP KEPUASAN KONSUMEN HYPERMART MANADO TOWN SQUARE - Danny David Mukuan (JURNAL ADMINISTRASI BISNIS, 2017)
The study titled Influence People, Physical Evidence and Process Against Consumer Satisfaction Hypermart Manado Town Square aims to determine the effect on the customer satisfaction, the influence of physical evidence to customer satisfaction, how to influence the process of consumer satisfaction, how Influence People, Physical Evidence and Process together on customer satisfaction, and where the most dominant variable from person, physical evidence, and prosess to customer satisfaction Hypermart Manado Town Square.            The results showed that the variable effect of 12.8 % on customer satisfaction, pyhysical evidence variable effect by 21.8 % on customer satisfaction, process variables influence of 27.3 % on customer satisfaction, the variables, physical evidence, and process together provide the effect of 35.6 % on customer satisfaction Hypermart Manado Town Square,  the result of partial test of the coefficient of determination is obtained that the process variable ( X3 ) that are the dominant influence. Manajemen must add him to the training of employees, give more attention in terms of direct physical can be enjoyed by consumer, and should pay more attention to the end of the service to consumers Hypermart Manado Town Square. Keywords : People, Physical Evidence, Process, Customer Satisfaction